Alkitab Menurut Gereja Katolik dan Protestan: Dari Keterpisahan menuju Kontekstualisasi - Denni H.R. Pinontoan (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2021)
This article discusses the views and beliefs of the Roman Catholic and Protestant Churches regarding the Bible. History shows the differences or separation between the two churches, especially the position of the Bible and tradition, but in the process of the ecumenical movement in which the efforts to accept and acknowledge each other, transcending the separation is a shared understanding of the meaning of the Bible for life. The discussion of this article concludes that in the differences that exist between the Catholic and Protestant churches regarding the position and belief in the Bible and tradition, in the historical dialectic, directly or indirectly, the beliefs of these two churches are about how the divine messages must continue to be contextualized in order to still meaningful for life together.